MENGENAL LEBIH DALAM APA ITU KAPABILITAS DINAMIK - James Rianto Situmorang (Business Administration Department - Universitas Katolik Parahyangan, 2018)
Dynamic capability is an idea initiated by Teece in 1997 based on the result of discussions with his students in the MBA Program at Stanford and Berkeley. Dynamic capability has been discussed for more than 20 years but dynamic capability has not been a popular study until now. Dynamic capability articles written by several experts are usually presented in terms and languages that are difficult for readers to understand. Some experts even asked and criticized the concept of dynamic capabilitiy. Whatever, dynamic capability can be carried out by a companiy as a way to have a competitive advantage. Company must take three steps according to Teece (2009), namely, sense, seize opportunities, and reconfigure company knowledge, competencies, and resources.